In-depth Assessment of Groundwater Quality in East Java Industrial Areas to Maintain the Sustainability of Groundwater Utilization - Hendrayana, Heru; Riyanto, Indra Agus; Nuha, Azmin (Brawijaya University, 2025)
With its abundant groundwater potential, East Java faces a growing risk of contamination due to rapid industrial growth. This study assessed groundwater quality in four regional groundwater basins (GWB) using the Water Quality Index (WQI), water quality standard comparison, Piper diagram, and hydrogeochemical ion analysis. The WQI analysis revealed that 59% of the samples were classified as excellent and good for consumption, predominantly found in volcanic, river alluvial, and limestone hill areas. In comparison, 11% were unsuitable for consumption due to contamination, particularly near coastal, industrial, and agricultural zones. The Piper diagram showed that most groundwater samples were unpolluted, reflecting the natural interaction between groundwater and surrounding lithology. However, ion standard comparison identified samples exceeding acceptable ion levels, and ion correlation analysis confirmed contamination from industrial, agricultural, anthropogenic, and municipal wastewater activities. These findings highlight the need for targeted groundwater management, particularly in areas vulnerable to contamination.